2015
DOI: 10.1116/1.4923275
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature growth of low friction wear-resistant amorphous carbon nitride thin films by mid-frequency, high power impulse, and direct current magnetron sputtering

Abstract: Low-temperature growth of low friction wear-resistant amorphous carbon nitride thin films by mid-frequency, high power impulse, and direct current magnetron sputtering, Journal of Vacuum Science & Technology. A, 2015, 33(5) The potential of different magnetron sputtering techniques for the synthesis of low friction and wear resistant amorphous carbon nitride (a-CN x ) thin films onto temperature-sensitive AISI52100 bearing steel, but also Si(001) substrates was studied. Hence, a substrate temperature of 150 C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 48 publications
6
13
0
Order By: Relevance
“…In HIPIMS, the intermittent energetic particle bombardment offers means for the growing material to relax, while the constant particle bombardment in case DCMS is used results in increasing compressive film stresses. This was also observed in [38]. Correspondingly, the relatively low stress values for films deposited in HiPIMS mode at 110 °C appear not significantly affected by the different inert gases.…”
Section: Dcms and Hipims At Substrate Temperatures Of 110 °C (Lt) As supporting
confidence: 58%
“…In HIPIMS, the intermittent energetic particle bombardment offers means for the growing material to relax, while the constant particle bombardment in case DCMS is used results in increasing compressive film stresses. This was also observed in [38]. Correspondingly, the relatively low stress values for films deposited in HiPIMS mode at 110 °C appear not significantly affected by the different inert gases.…”
Section: Dcms and Hipims At Substrate Temperatures Of 110 °C (Lt) As supporting
confidence: 58%
“…The significant increase of the hardness of the composites compared to the reference graphite sample can be attributed to the increased density and decreased porosity of the composites after the infiltration (Table II) [44]. This is a result of the deposition of hard SiC and Si3N4 particles in the pores of the soft graphitic matrix, contributing to the measured hardness values, which is confirmed by the relatively high errors of the measurements.…”
Section: Accepted Manuscriptmentioning
confidence: 55%
“…The results show that the surface roughness Sa range from 3.32 nm to 44.6 nm. (2) Orthogonal experiment was arranged to analyze the process parameters. The results show that the parameters affect the film surface roughness in the following orders: nitrogen pressure, duty ratio, target current and bias voltage according to range analysis and visual analysis.…”
Section: Resultsmentioning
confidence: 99%
“…CNx films have a good application prospect in industrial production and biomedicine for its excellent properties [1,2], such as the high hardness, low friction coefficient, good biocompatibility, wear resistance, and so on. Many studies have shown that the process parameters and the preparation technology have a great influence on thin film structure and friction performance.…”
Section: Introductionmentioning
confidence: 99%